(untitled) (Biodiversitas Journal of Biological Diversity, 2011)
Susanti R (2011) Polymorphic sequence in the ND3 region of Java endemic Ploceidae birds mitochondrial DNA. Biodiversitas 12: 70- 75. As part of biodiversity, Ploceidae bird family must be kept away from extinction and degradation of gene-diversity. This research was aimed to analyze ND3 gene from mitochondrial DNA of Java Island endemic of Ploceidae bird. Each species of Ploceidae birds family was identified based on their morphological character, then the blood sample was taken from the birds nail vein. DNA was isolated from blood using Dixit method. Fragment of ND3 gene was amplified using PCR method with specific primer pairs and sequenced using dideoxy termination method with ABI automatic sequencer. Multiple alignment of ND3 nucleotide sequences were analyzed using ClustalW of MEGA-3.1 program. Estimation of genetic distance and phylogenetic tree construction were analyzed with Neighbor-Joining method and calculation of distance matrix with Kimura 2 –parameter. The result of Java Island endemic of Ploceidae bird family exploration showed that Erythrura hyperythra and Lonchura ferruginosa can not be found anymore in nature, but the Lonchura malacca that are not actually Java island endemic was also found. Nucleotide sequence of mitochondrial ND3 gene of Ploceidae bird family showed a quite high polymorphism, with 122 substitutions from 334 nucleotides analyzed. Phylogenetic tree of nucleotide sequence of Ploceidae bird family formed 2 clusters. One cluster consisted of the Ploceus hypoxanthus, Ploceus philippinus, Ploceus manyar and Passer montanus, and the others species were included in the second cluster. ND3 gene sequence data from this Ploceidae family need to be analyzed further to see possible relationship with a particular phenotype.